A study of quiet eye's phenomenon in the shooting section of "laser run" of modern pentathlon. Issue 6 (15th November 2018) - Chirico, Andrea; Fegatelli, Dario; Galli, Federica; Mallia, Luca; Alivernini, Fabio; Cordone, Susanna; Giancamilli, Francesco; Pecci, Stefano; Tosi, Gian Marco; Giordano, Antonio; Lucidi, Fabio; Massaro, Mina
Abstract: The aim of the study was to evaluate the effects of the Quiet eye (QE) phenomenon on performances during the shooting section of "Laser Run" of Modern Pentathlon, in two samples of athletes (novices and experts). The "Laser Run" consists of running and shooting activities. The study involved 18 experienced athletes of the Italian National Team of Modern Pentathlon (i.e., "elite" group) and 18 young and nonexpert athletes of a local Pentathlon club (i.e., "novice" group). Participants performed, in ecological conditions, five trials of four series of shootings (as it occurs in the real competitions), for a total of 20 series. During the shooting trials, athletes wore a mobile Eye Tracking System to record eye movements (saccades, blinks, and fixations). Key measures of the study were QE parameters (QE Duration [QED], Relative QED [RQED], and QE Onset), as well as the performance (accuracy and time to perform the event). The results revealed that both groups of athletes had a longer QED, RQED, and an earlier onset during their best shots than during the worse ones. Furthermore, differences between the groups showed that elite athletes had an earlier onset and a shorter QED than the novice group of athletes. These results provide insightful information about different cognitive and perceptual processes involved in Modern Pentathlon's athletes' performances at both the elite and non‐elite level. Abstract : The study is the first evaluating visual behavior in the "Laser Run" section of modern pentathlon in elite athletes. The results provide insightful information about different cognitive and perceptual processes involved in Modern Pentathlon's athletes' performances at both elite and non‐elite level.